KUALITAS HADIS TENTANG TAWAF IFADAH BAGI PEREMPUAN HAID (Studi Kritik Sanad) - Amin, Muhammad (TAZKIR: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2014)
AbstractHadith is the second source of law in Islam although its codification accomplished in the year 100 AH, which at that time there has been a lot going on hadith forgeries. Likewise Hadith tawaf Ifadah for women menstruation should be investigated because hadith ahad and its quality has not been thoroughly studied by the perfect rules. This study indicates that the sanad of hadith tawaf Ifadah of women's menstruation is sahih lighairi.Kata kunci : Kulitas, Hadis, Tawaf Ifadah